2011
DOI: 10.1093/brain/awr311
|View full text |Cite
|
Sign up to set email alerts
|

Executive deficits are related to the inferior frontal junction in early dementia

Abstract: Executive functions describe a wide variety of higher order cognitive processes that allow the flexible modification of thought and behaviour in response to changing cognitive or environmental contexts. Their impairment is common in neurodegenerative disorders. Executive deficits negatively affect everyday activities and hamper the ability to cope with other deficits, such as memory impairment in Alzheimer's disease or behavioural disorders in frontotemporal lobar degeneration. Our study aimed to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
71
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 86 publications
(173 reference statements)
13
71
1
1
Order By: Relevance
“…It is not clear why a more impaired PCT or CDT in the beginning of the disease predicts an earlier death. Brain imaging studies have shown that visuospatial/constructional abilities are associated with the parietal cortex [30] and that executive functioning is associated with the anterior cingulate/posterior medial frontal cortex and lateral prefrontal cortices [31]. It has been hypothesized that increased cholinergic deficits and/or a higher Lewy body load in these brain regions can lead to more pronounced visuospatial/constructional or executive dysfunction [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear why a more impaired PCT or CDT in the beginning of the disease predicts an earlier death. Brain imaging studies have shown that visuospatial/constructional abilities are associated with the parietal cortex [30] and that executive functioning is associated with the anterior cingulate/posterior medial frontal cortex and lateral prefrontal cortices [31]. It has been hypothesized that increased cholinergic deficits and/or a higher Lewy body load in these brain regions can lead to more pronounced visuospatial/constructional or executive dysfunction [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Executive function is specifically associated with the frontal lobes [18,19], which are highly susceptible to age-related changes compared to other areas associated with cognitive function [19,20,21]. Furthermore, caffeine is an adenosine receptor antagonist [22].…”
Section: Discussionmentioning
confidence: 99%
“…The nature of working memory makes it subject to distractibility and interference, and it declines in conditions of stress and in psychiatric and neurological diseases (e.g., schizophrenia, Alzheimer's disease) (Barch and Ceaser 2012;Schroeter et al 2012). Moreover, working memory underlies other cognitive processes, such as long-term memory and language, amongst others, which also can become impaired with age and disease Bizon et al 2012).…”
Section: Working Memorymentioning
confidence: 99%